2021
DOI: 10.1021/acs.nanolett.1c02565
|View full text |Cite
|
Sign up to set email alerts
|

Supercurrent and Phase Slips in a Ballistic Carbon Nanotube Bundle Embedded into a van der Waals Heterostructure

Abstract: We demonstrate long-range superconducting correlations in a several-micrometers-long carbon nanotube bundle encapsulated in a van der Waals stack between hBN and NbSe 2 . We show that a substantial supercurrent flows through the nanotube section beneath the NbSe 2 crystal as well as through the 2 μm long section not in contact with it. The large in-plane critical magnetic field of this supercurrent is an indication that even inside the carbon nanotube Cooper pairs enjoy a degree of paramagnetic protection typi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The parity of the layer number N and the lattice orientation is determined, a posteriori , by second harmonic generation (SHG) measurements for all samples. NbSe 2 crystals are fully encapsulated in hBN 30 and edge contacts are fabricated by electron beam lithography 31 . A 250 nm-long channel of 250 nm width is patterned by electron beam lithography and reactive ion etching.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parity of the layer number N and the lattice orientation is determined, a posteriori , by second harmonic generation (SHG) measurements for all samples. NbSe 2 crystals are fully encapsulated in hBN 30 and edge contacts are fabricated by electron beam lithography 31 . A 250 nm-long channel of 250 nm width is patterned by electron beam lithography and reactive ion etching.…”
Section: Resultsmentioning
confidence: 99%
“…The dashed white contour highlights the NbSe 2 crystal. Electrodes are fabricated by edge contact techniques 27 , 31 , 47 , while the constrictions are made by reactive ion etching. The yellow arrow indicates the supercurrent pathway.…”
Section: Resultsmentioning
confidence: 99%
“…[ 386 ] Bäuml et al have since demonstrated supercurrent and phase slips in a bundle of CNTs encapsulated by h‐BN and 2D NbSe 2 . [ 387 ] These recent results indicate promise for CNTs in superconductor–semiconductor hybrid devices and—potentially—also for confirming presence of Majorana states in devices.…”
Section: Topological Qubits and Superconductor–semiconductor Hybrid D...mentioning
confidence: 89%
“…Recently, Desjardins et al used a proximal ferromagnetic multilayer to enhance spin-orbit coupling in a CNT contacted by superconducting electrodes; they observed oscillations of sub-gap states with applied magnetic field and a zero-bias peak [385] . Bäuml et al have since demonstrated supercurrent and phase slips in a bundle of CNTs encapsulated by h-BN and 2D NbSe2 [386] . These recent results indicate promise for CNTs in superconductor-semiconductor hybrid devices and -potentially -also for confirming presence of Majorana states in devices.…”
Section: Hybrid Semiconductor-superconductor Devicesmentioning
confidence: 99%
“…Phase slip has been observed in exfoliated NbSe 2 layers [27,28], a 2D Ising superconductor with a critical temperature of T C = 7 K [29,30], by DC measurement and by RF radiation assisted Josephson junction like Shapiro steps. In former studies, uncontrollable disorders in a NbSe 2 layer [27,28] or its junction with a different material [31] have contributed to the phase slip events. It still remains an issue how to use an artificially-stacked homojunction of 2D superconductors to manipulate the order parameter and its topological fluctuation for superconducting quantum device applications.…”
mentioning
confidence: 99%